Kegiatan Ekstrakurikuler Drum Band Di SMP Negeri 29 Padang - jihan, Jihan Chaniago; Esy Maestro (Universitas Negeri Padang, 2023)
This study aims to describe how the process of extracurricular drum band activities at SMP Negeri 29 Padang. This type of research is qualitative research that uses descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments stationery, cameras and voice recorders. Data collection techniques in this study are observation, interviews, documentation and literature studies. The steps of analyzing data are collecting data, identifying data and drawing conclusions. The result of this study is that in recruiting drum band members, coaches and coaches do not select members first so that students are free to choose the instruments they want to take, this has an impact on the imbalance between melodic and percussion players. The extracurricular drum band activities at SMP Negeri 29 Padang every week are the same, it's just that there are differences in song selection. Activities on Friday the coach focuses more on students to understand the song and practice according to the instrument first so that students can master the new song that will be played simultaneously later and on Saturday the coach combines all members of the drum band to do combined exercises.